Recent Trends in Top-Down Technologies for the Preparation of Nanosuspensions - Kodipyaka, Ravinder; Govindu, Sumalatha (Indian Journal of Pharmaceutical Education and Research, 2025)
The increasing demands for drugs and advancements in drug discovery have led to the development of numerous potent molecules with unfavourable solubility and bioavailability characteristics. These challenges are driving significant developments in formulation technologies, such as nanosuspensions, which can potentially address these challenges and improve the success rate of new molecules. Nanosuspensions have unique properties due to their size, which can enhance solubility, adapt to surface modification and mucoadhesion for drug targeting. However, key aspects to consider when designing nanosuspensions include stability in liquid and solid states and dispersibility without aggregation. Multiple techniques and formulation approaches are employed to design and develop nanosuspension formulations with desired characteristics. Top-down methods such as media milling and high-pressure homogenization have drawn interest from researchers in both academia and the pharmaceutical industry due to their high level of adoptability and scalability. As a result, numerous innovative oral and parenteral formulations are being developed, reaching patients globally and serving their unmet needs.
Keywords: Nanosuspension; Solubility and bioavailability enhancement; Preparation methods; Formulation considerations; Characterization techniques.